Oral administration of modified live canine parvovirus type 2b induces systemic immune response. Issue 2 (10th January 2020) - Cavalli, A.; Desario, C.; Marinaro, M.; Losurdo, M.; Camero, M.; Decaro, N.; Catella, C.; Lanave, G.; Buonavoglia, C.
Highlights: Interfering MDA levels can hamper the immune response against CPV-2 vaccination. Fourteen pups with different MDA titres were orally administered an MLV CPV-2b vaccine. All pups but one seroconverted after a single vaccine administration. The remaining pup raised an immune response after the second vaccination. Oral administration of CPV-2 vaccines can help overcome MDA interference. Abstract: Different strategies have been proposed to overcome maternally derived antibody (MDA) interference with canine parvovirus type 2 (CPV-2) immunisation, including intranasal vaccination, which presents some practical limitations. In the present study, the results of the oral administration of a commercial CPV-2b modified live virus (MLV) vaccine in pups with MDA are reported. The CPV-2b vaccine was orally administered to 14 6-week-old pups with a bait. Blood samples and rectal swabs were collected at different days post-vaccination (dpv) to determine CPV-2 antibody titres and DNA loads. Thirteen pups were positive to serological and virological tests after the first vaccination and one pup became positive after the second vaccine administration. The findings of this study suggest that systemic immunity against CPV-2 may be achieved by the use of an MLV CPV-2b vaccine administered orally even in the presence of MDA titres that usually interfere with vaccination.